2017
DOI: 10.1159/000478977
|View full text |Cite
|
Sign up to set email alerts
|

Replication Protein A 3 Is Associated with Hepatocellular Carcinoma Tumorigenesis and Poor Patient Survival

Abstract: Background: Replication protein A (RPA) 3 is a subunit of the RPA protein complex, which functions in multiple processes of DNA metabolism. Dysregulation of RPA1 and RPA2 has been implicated in tumor progression in several cancer types. However, the function of RPA3 in hepatocellular carcinoma (HCC) tumorigenesis has not been elucidated. Method: In this study, we investigated the function of RPA3 in HCC development by stably knocking down its expression using short hairpin RNA (shRNA) in HepG2 cell line, follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…[ 9 ] These findings implicate that RPA1 might play an important role in regulating the activation of EBV and host immune response against its infection, [ 18 ] while the underlying mechanisms are yet to be addressed. In addition, previous studies have demonstrated the expression of RPA1 and RPA2 are potential prognostic factors in multiple cancers, [ 17c,19 ] and likewise, RPA3 has been associated with survival of patients with gastric cancer, [ 20 ] hepatocellular cancer, [ 21 ] and NPC. [ 22 ] These findings suggest that RPA1 and other subunits of RPA complex might be important modulators for the progression of several human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] These findings implicate that RPA1 might play an important role in regulating the activation of EBV and host immune response against its infection, [ 18 ] while the underlying mechanisms are yet to be addressed. In addition, previous studies have demonstrated the expression of RPA1 and RPA2 are potential prognostic factors in multiple cancers, [ 17c,19 ] and likewise, RPA3 has been associated with survival of patients with gastric cancer, [ 20 ] hepatocellular cancer, [ 21 ] and NPC. [ 22 ] These findings suggest that RPA1 and other subunits of RPA complex might be important modulators for the progression of several human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…RPA3, a member of the replication protein family, plays an important role in DNA repair, recombination, replication, and cell cycle regulation. RPA3 is associated with the occurrence and poor prognosis of liver cancer, as well as the aging of hematopoietic stem cells (Xiao et al, 2018;Lian X. et al, 2019;Zhang and Yu, 2020). RRM2 has been reported to be associated with the occurrence and poor survival of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…An early study aiming to identify autoantigens in breast cancer patients showed that antibodies against RPA32 can be detected prior to diagnosis [22]. In hepatocellular carcinoma and gastric cancer, higher RPA14 expression was found to correlate with a poor outcome [23,24]. Another study in bladder cancer showed that while in early stage low RPA32 levels positively correlated with patient outcome, at later stages in invasive tumors, both high RPA70 and RPA32 expression informed adverse prognosis [25].…”
Section: Discussionmentioning
confidence: 99%